Cholesterol and Melatonin Exert Opposite Effects on the Interaction of Model DMPC Membranes with the SARS‐CoV‐2 S‐Protein: A SANS Study. Issue 1 (13th April 2023) - Bulavin, Leonid A.; Soloviov, Dmytro V.; Ivankov, Oleksandr I.; Doroshenko, Iryna Yu.; Onuk, Marta M.; Nikolaenko, Tymofii Yu.
Abstract: An effect of receptor‐binding domain (RBD) of SARS‐CoV‐2 S‐protein on structural parameters of model lipid membranes presented by dimyristoylphosphatidylcholine (DMPC) systems with cholesterol and melatonin impurities is studied by small angle neutron scattering (SANS). It is shown that an increase in melatonin concentration in the lipid membrane leads to a decrease in the thickness of the lipid bilayer, while an increase in the concentration of cholesterol leads to an increase in its thickness. It is suggested that increasing the concentration of melatonin in a membrane prevents the interaction of coronaviral S‐protein with a lipid membrane of a cell. In the presence of cholesterol in the system, the interaction of a lipid membrane with an active part of S‐protein occurs depending on a phase state of the lipid: in the case of a gel phase, there is no changes in structural parameters, but at higher temperatures in the case of a liquid crystal phase, an addition of RBD SARS‐CoV‐2 to the system causes a reduce in the membrane thickness.